Pemanfaatan RSSI Pada Ponsel Pengunjung Dalam Menghitung Jarak Terhadap Transmitter Wifi Pada Ruang Baca Perpustakaan Politeknik Negeri Malang - Monica Wahyuni; Mila Kusumawardani; Rachmad Saptono (Politeknik Negeri Malang, 2022)
The pandemic period caused by the coronavirus disease causes restrictions on the number of users in a room to minimize the spread, for example, libraries. The library is a room area that can cause virus transmission when crowds of visitors. A system is needed to provide information regarding the number of library visitors. Utilizing a network (wifi transmitter) available in the library can provide information on the number of visitors based on the number of network users in a room. Utilization of the network (wifi transmitter) can be in the form of a positioning system by utilizing the wifi signal beam received by the user in RSSI (Received Signal Strength Indicator). To calculate the estimated user position, a trilateration method is used based on the placement of three wifi transmitters. The library visitor positioning system consists of users as wifi transmitter users and admins. At the X-coordinate, the measuring point with a low deviation of the measurement value is indicated by points C and E with a value of 0.1. The large deviation of the measurement value is indicated by the P point of 4.5. At the Y coordinate, point O has a low deviation value of 1.25, and the largest deviation value is at point M of 5.6. The accuracy of the X coordinate shows a value of 97.647% and at the Y coordinate of 96.57%. Both coordinates have good accuracy for the points used as position measurements.